Effect of thinner inhalation on lipid peroxidation and some antioxidant enzymes of people working with paint thinner - Halifeoglu, I; Canatan, H; Ustundag, B; Ilhan, N; Inanc, F (John Wiley & Sons Ltd, 2000)
Paint thinner is a commonly used industrial solvent with considerable potential for abuse by inhalation. Paint thinner is taken into the body by inhalation or by contact with the skin. Paint thinner is oxidized gradually by cytochrome P450-dependent monooxygenase and consequently free radicals are produced. In the present study we measured plasma malondialdehyde (MDA, a product of lipid peroxidation) levels as an indicator of oxidative damage and activity levels of antioxidant enzymes gluthatione peroxidase (GSH-Px) and superoxide dismutase (SOD) in erythrocytes of a group of people (n = 18) working with paint thinner. The control group was composed of 18 healthy adults. There was a statistically significant (p < 0.001) increase in MDA (2.0+/-0.7 nmol ml(-1)) and GSH-Px (86.5+/-16.6 U g(-1) Hb) activity levels in people working with paint thinner compared with control subjects (MDA: 1.0+/-0.3 nmol ml(-1); GSH-Px: 53.9+/-14.5 U g(-1) Hb). Similarly, there was also an increase (p < 0.05) in the SOD levels (1079+/-214.6 U g(-1) Hb) of people working with paint thinner compared with controls (953.3+/-46.7 U g(-1) Hb). Based on our results, it can be concluded that paint thinner inhalation may increase lipid peroxidation and consequently induce antioxidant enzymes. Copyright (C) 2000 John Wiley & Sons, Ltd.
Keywords: paint thinner; MDA; SOD; GSH-Px